BODY IMAGE MAHASISWA GIZI SERTA KAITANNYA DENGAN ASUPAN ENERGI DAN STATUS GIZI Body Image of Nutrition College Students and its Association with Energy Intake and Nutritional Status - Alifatuz Zahrah; Lailatul Muniroh (Universitas Airlangga, 2020)
Nutrition college students as a representatives in society is required to have ideal and healthy body. Besides aff ected by those demands, body image is also aff ected by nutritional status and energy intake. A good knowledge of nutrition is not always followed by appropriate practices as well as normal nutritional status and average energy intake. This research was aimed to analyze the relationship of energy intake and nutritional status with body image of nutrition college students of Universitas Airlangga. This research was an observational analytic study using cross sectional design. The sample size were 71 nutrition college student, taken by proportional random sampling. The observed variables were body image, energy intake, and nutritional status. Datas were analyzed used the Pearson correlation test, Spearman correlation test, and Chi Square. The results showed that 54.9% of nutrition college students had negative body image perception, normal energy intake (52.1%), and normal nutritional status (67.6%). There was correlation between body image with energy intake (p = 0.007) and nutritional status (p = 0.001). It is concluded that high intake of energy and overweight may leads to negative body image. Nutrition college students should make the right eff ort in achieving their desired ideal body weight through manage their food intake and doing weight monitoring routinely